Characterization and application of a lytic jumbo phage ZPAH34 against multidrug-resistant Aeromonas hydrophila - Hou, Yuting; Wu, Zhihao; Ren, Li; Chen, Yuan; Zhang, Yong-An; Zhou, Yang (Frontiers in Microbiology, 2023)
Aeromonas hydrophila is an emerging foodborne pathogen causing human gastroenteritis. Aeromonas species isolated from food such as seafood presented multidrug-resistance (MDR), raising serious concerns regarding food safety and public health. The use of phages to infect bacteria is a defense against drug-resistant pathogens. In this study, phage ZPAH34 isolated from the lake sample exerted lytic activity against MDR A. hydrophila strain ZYAH75 and inhibited the biofilm on different food-contacting surfaces. ZPAH34 has a large dsDNA genome of 234 kb which belongs to a novel jumbo phage. However, its particle size is the smallest of known jumbo phages so far. Based on phylogenetic analysis, ZPAH34 was used to establish a new genus Chaoshanvirus. Biological characterization revealed that ZPAH34 exhibited wide environmental tolerance, and a high rapid adsorb and reproductive capacity. Food biocontrol experiments demonstrated that ZPAH34 reduces the viable count of A. hydrophila on fish fillets (2.31 log) and lettuce (3.28 log) with potential bactericidal effects. This study isolated and characterized jumbo phage ZPAH34 not only enriched the understanding of phage biological entity diversity and evolution because of its minimal virion size with large genome but also was the first usage of jumbo phage in food safety to eliminate A. hydrophila.